Cultural capital as a predictor of school success: evidence and gender differences in Chinese middle schools - Hui Jin; Shi Jiao; Xu Ma; Yunan Xia (Humanities & Social Sciences Communications, 2024)
Abstract Cultural capital is vital for equitable educational development. This paper studies the effect of family cultural capital on the performance of middle school students with regard to gender, using a multiple linear regression model. Participants from four representative middle schools, totalling 1036 students, were selected during the online learning period. The study found that institutionalised and objectified cultural capital had a pronounced positive effect on students’ school outcomes, but cultural capital that was embodied had both positive and negative effects. Significant differences in the effects of cultural capital on school success were found between male and female students. The educational level of a mother has a significant impact on the school attainment of female students in Chinese, English, math and overall achievement, whereas a father’s education level has a significant effect on male students’ English achievement and overall achievement. The results of the study showed that cultural capital contributed to the academic success of middle school students in different ways. The results presented above contribute to a better comprehension of the mechanisms of the influence of cultural capital on the school performance of middle school students, which has important implications for students’ educational equity. This study recommends improving the mechanism of collaborative education among schools, families and society, by paying attention to vulnerable groups that lack cultural capital, improving the methods of educational evaluation and providing tailor-made education for all types of students.